Oral and Intestinal Bacterial Substances Associated with Disease Activities in Patients with Rheumatoid Arthritis: A Cross-Sectional Clinical Study. (18th February 2022) - Kitamura, Kaori; Shionoya, Hiroshi; Suzuki, Suguru; Fukai, Richio; Uda, Shinichi; Abe, Chiyuki; Takemori, Hiromitsu; Nishimura, Keita; Baba, Hisashi; Katayama, Kou; Terato, Kuniaki; Waritani, Takaki
Abstract : Intestinal bacterial compositions of rheumatoid arthritis (RA) patients have been reported to be different from those of healthy people. Dysbiosis, imbalance of the microbiota, is widely known to cause gut barrier damage, resulting in an influx of bacteria and their substances into host bloodstreams in animal studies. However, few studies have investigated the effect of bacterial substances on the pathophysiology of RA. In this study, eighty-seven active RA patients who had inadequate responses to conventional synthetic disease-modifying antirheumatic drugs or severe comorbidities were analyzed for correlations between many factors such as disease activities, disease biomarkers, intestinal bacterial counts, fecal and serum lipopolysaccharide (LPS), LPS-binding protein (LBP), endotoxin neutralizing capacity (ENC), and serum antibacterial substance IgG and IgA antibody levels by multiple regression analysis with consideration for demographic factors such as age, sex, smoking, and methotrexate treatment. Serum LBP levels, fecal LPS levels, total bacteria counts, serum anti-LPS from Porphyromonas gingivalis (Pg-LPS) IgG antibody levels, and serum anti-Pg-LPS IgA antibody levels were selected for multiple regression analysis using Spearman's correlation analysis. Serum LBP levels were correlated with disease biomarker levels, such as erythrocyte sedimentation rate (p < 0.001 ), C-reactive protein (p < 0.001 ), matrix metalloproteinase-3 (p < 0.001 ), and IL-6 (p = 0.001 ), and were inversely correlated with hemoglobin (p = 0.005 ). Anti-Pg-LPS IgG antibody levels were inversely correlated with activity indices such as patient global assessments using visual analogue scale (VAS) (p = 0.002 ) and painVAS (p < 0.001 ). Total bacteria counts were correlated with ENC (p < 0.001 ), and inversely correlated with serum LPS (p < 0.001 ) and anti-Pg-LPS IgA antibody levels (p < 0.001 ). These results suggest that substances from oral and gut microbiota may influence disease activity in RA patients.